Comparison between Pooled Sera and Coomercial Serum on the Accuracy of Triglyceride Assessment - Sari, Yulia Ratna; Jesica, Fanny; Niken, Niken (PT. Riset Press International, 2023)
The increase in dyslipidemia cases every year requires the Clinical Chemistry laboratory to carry out quality control which is influenced by an assessment of accuracy and accuracy. These measurements were used with control materials. So far, in laboratories, there are still many commercial serum control materials used as controls that are used daily in triglyceride tests, and rarely use pooled sera. In fact, there are several advantages in using pooled sera as a control material. This type of analytic survey research with a comparative study method. The sampling technique used is purposive sampling. Data collection techniques were carried out using observation sheets. Data were processed computerized using univariate analysis and bivariate analysis using independent t-tests. The results showed that the average triglyceride examination value with Pooled Sera control material was 94.67 mg/dL with a Standard Deviation of 2.52, a coefficient value variance of 2.66%. While the results of triglyceride examination with Commercial Serum control material were 79.13 mg/dL with a Standard Deviation of 3.57, the coefficient of variance was 4.51%. It was concluded that there is a significant difference between triglyceride examination using Pooled Sera and Commercial Serum. It is recommended that there be developments in medical laboratory technology in hospitals, making this research a reference in educational institutions, and further research on other parameters between Pooled Sera ingredients and other Serum.